A critical analysis of the job instability in platform economy - Gallego Losada, Rocío (Lex Social: Revista de Derechos Sociales, 2021)
This article reflects on the vulnerability of the new digital platform workers regarding their social rights, a highly controversial issue at the doctrinal and jurisprudential levels. Firstly, we analyse the greater job instability and lack of protection experienced by the workers in this type of platforms, and the labour legal framework that derives from these new business models. In this sense, the current doctrine can be grouped into two positions: a first one which defends that these workers should be considered employees and, therefore, remain under the umbrella of the general labour legislation; and a second one, that proposes a legal transformation to include these special workers. Secondly, we analyse the effects derived from the growing development of the platform economy for the Spanish Social Security system. This analysis focuses both on the effects of the protective action of the welfare state for their workers, as well as on its impact on the financing of the public pension system. The article draws a series of final conclusions warning about the possible crash of the fundamental social rights of platform workers.